Internal Controls Over Trade Stock at The UIKA Bogor Employees’ Cooperative for The Period 2025 - Akmal Setya Nugraha; Indupurnahayu Indupurnahayu; Rasiman Rasiman (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2026)
This analysis aims to evaluate the inventory recording and control systems at the Ibn Khaldun University Employees Cooperative (KIKA). The cooperative employs a perpetual inventory method and implements internal controls over inventory. The researcher conducted a study using the stock valuation method to determine the total inventory value related to the management of trading stock, particularly with a view to improving the productivity of the inventory rate budgeted by the cooperative. This case study is of a descriptive nature, presenting information based on calculations that detail the inventory management applied at the cooperative and comparing these findings. The research results indicate that although the recording system has been computerised, there are still weaknesses in inventory classification and control, which have the potential to cause discrepancies. Data analysis for the period from January to July 2025 shows a significant increase in the cost of goods sold (COGS), caused by a rise in the volume of merchandise purchases. The presentation of inventory in the cooperative’s financial statements still reflects a detailed classification of inventory. The cooperative is continuously strengthening its internal control systems and developing a more structured inventory information system to support more effective and accountable managerial decision-making.